Effect of Au Nanoparticle Agglomeration on SERS Signal Amplification - Kirill Khabarov; Emiliia Filalova; Messan Nouraldeen; Ekaterina Kameneva; Andrey Musaev; Sergei Tikhonov; Victor Ivanov (Nanomaterials, 2023)
An analyzed substance’s signal intensity and detection sensitivity in surface-enhanced Raman spectroscopy (SERS) significantly depend on the size and agglomeration degree of nanoparticles (NPs) forming the enhancing structure. Structures were manufactured by aerosol dry printing (ADP), where NPs’ agglomeration depends on printing conditions and additional particle modification techniques. The influence of agglomeration degree on SERS signal enhancement was studied in three types of printed structures using the methylene blue model molecule as an analyte. We demonstrated that the ratio between individual NPs and agglomerates in a studied structure strongly affects SERS signal amplification, and structures formed mainly from non-agglomerated NPs enhance the signal better. In this sense, aerosol NPs modified by pulsed laser radiation provide better results than thermally modified NPs, since in laser modification a larger number of individual NPs is observed due to the absence of secondary agglomeration effects in the gas stream. However, increasing gas flow may minimize the secondary agglomeration, since the time allotted for the agglomeration processes is reduced. In this paper, we show how different NPs’ agglomeration tendencies influence SERS enhancement to demonstrate the process of using ADP to form inexpensive and highly efficient SERS substrates with huge application potential.